Pengaruh Program Gerakan Gemar Membaca terhadap Peningkatan Minat Baca di SMKN 4 Padangsidimpuan (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the effect of the Gerakan Gemar Membaca (Love to Read Movement) program on improving students' reading interest at SMK N 4 Padangsidimpuan. The research employed a quantitative approach with an experimental design, involving two groups: the experimental group participating in the Gerakan Gemar Membaca program and the control group not participating. A purposive sampling technique was used, with a total of 60 students, 30 in each group. The data collection instrument was a questionnaire measuring reading interest, administered before and after the program, along with observations of literacy activities. The collected data were analyzed using a t-test to compare the pre-test and post-test scores between the two groups. The results showed a significant improvement in the experimental group, with the average post-test score reaching 78.00, while the control group scored an average of 65.00. This indicates that the Gerakan Gemar Membaca program has a positive impact on enhancing students' reading interest. The study concludes that the implementation of literacy programs such as Gerakan Gemar Membaca is effective in improving students' reading interest in secondary schools. Therefore, it is recommended that the program be continued and expanded to foster a stronger reading culture among students.